2021
DOI: 10.1055/s-0041-1731640
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Opioid Use Following Surgery for Symptomatic Neuroma

Abstract: Background Identifying patients at risk for prolonged opioid use following surgery for symptomatic neuroma would be beneficial for perioperative management. The aim of this study is to identify the factors associated with postoperative opioid use of >4 weeks in patients undergoing neuroma surgery. Methods After retrospective identification, 77 patients who underwent surgery for symptomatic neuroma of the upper or lower extremity were enrolled. Patients completed the Patient-Reported Outcomes Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…30 Although these data are limited, symptomatic neuromas reduce patient quality of life, increase the risk of developing an opioid misuse disorder, may lead to multiple additional operations, and lead to donor-site allodynia and other complications such as infection. 59,61–67 Finally, the procedure cost analysis demonstrated that overall allograft costs are lower than autograft costs in the inpatient setting and comparable in the outpatient setting. This suggests that allograft repair may achieve similar outcomes at similar or lower costs as compared with autograft repair.…”
Section: Discussionmentioning
confidence: 95%
“…30 Although these data are limited, symptomatic neuromas reduce patient quality of life, increase the risk of developing an opioid misuse disorder, may lead to multiple additional operations, and lead to donor-site allodynia and other complications such as infection. 59,61–67 Finally, the procedure cost analysis demonstrated that overall allograft costs are lower than autograft costs in the inpatient setting and comparable in the outpatient setting. This suggests that allograft repair may achieve similar outcomes at similar or lower costs as compared with autograft repair.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, it has been described that surgical treatment of a neuroma can improve the patient reported depression score 27 . Individuals with neuroma are also at risk for longer opioid use, where surgery can reduce the use of such drug in individuals 28 . However, long-term use of opioids and gabapentinoid drugs (e.g., gabapentin or pregabalin) are not known among individuals with neuroma irrespective of surgery being performed or not.…”
Section: Discussionmentioning
confidence: 99%
“…Neurolysis, or decompression, with or without coverage of a neuroma-in-continuity with flaps or tissue, is also utilized 25,26 . A common indication for neuroma surgery is neuropathic pain after a nerve injury, which should be related to a risk of depression or sleeping problems, affecting wellbeing 27,28 . The number of surgical procedures for neuroma treatment, and severity of preoperative and postoperative pain, have an impact on the Disability of the Arm, Shoulder and Hand (DASH) score 29 .…”
Section: Neuromas Cause Severe Residual Problems At Long-term Despite...mentioning
confidence: 99%
“…3–7 These procedures have been shown to aid in the reduction of pain and opioid use, while improving function and quality of life in patients treated for symptomatic neuromas. 2,8–11…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] These procedures have been shown to aid in the reduction of pain and opioid use, while improving function and quality of life in patients treated for symptomatic neuromas. 2,[8][9][10][11] Neuromas can sometimes be challenging to locate intraoperatively. Our group has observed a heightened physiologic response when dissecting in proximity to the symptomatic neuroma, despite general anesthesia.…”
Section: Introductionmentioning
confidence: 99%